4(x+6)/3=2x-5

Simple and best practice solution for 4(x+6)/3=2x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+6)/3=2x-5 equation:



4(x+6)/3=2x-5
We move all terms to the left:
4(x+6)/3-(2x-5)=0
We get rid of parentheses
4(x+6)/3-2x+5=0
We multiply all the terms by the denominator
4(x+6)-2x*3+5*3=0
We add all the numbers together, and all the variables
4(x+6)-2x*3+15=0
We multiply parentheses
4x-2x*3+24+15=0
Wy multiply elements
4x-6x+24+15=0
We add all the numbers together, and all the variables
-2x+39=0
We move all terms containing x to the left, all other terms to the right
-2x=-39
x=-39/-2
x=19+1/2

See similar equations:

| 6d−​2/11​​=2d−​2/​13 | | 8z-7-3z=7+5z | | 3y-18=24 | | 6d−​2÷11​​=2d−​2÷13 | | 3m-2=-25 | | X×5+y×8=170 | | 8-3(x+20)=2(4-3x)-4.5 | | 3(x+5)=2(3x+12 | | 2-1/2n=3n-16 | | -38=5u-8 | | 26.00+23.25x=59.00+17.75x | | -3(p+2)=-24 | | 3(x+8)=7(x-12) | | x=126=120 | | 2.3n-3.2+4.1=-6 | | 14b+15b=12b-15b | | 7b^2-9b+2=0 | | 90-x/5=11 | | 4x-5=-x+2(x+2) | | 3+2r=5r+2 | | 2.4k+8+3.6k=−7 | | 3/4n+1/2=6 | | 1/4x+9=22 | | (n+1)+(n+1+1)=27 | | |5v+8|=|5v+7| | | 4(3x+1)=8x-12 | | (−2g+7)−(g+11)=(−2g+7)−(g+11) | | 6(n-3)=4(n+2,1) | | 20n-1.5(2)=117 | | (−2g+7)−(g+11)(−2g+7)−(g+11=) | | 4x-15=82 | | (5x-5)+(3x+13)=180 |

Equations solver categories